Cardiac Resynchronisation Therapy and Cellular Bioenergetics: Effects Beyond Chamber Mechanics. Issue 1 (April 2019) - Antoniou, Christos-Konstantinos; Manolakou, Panagiota; Magkas, Nikolaos; Konstantinou, Konstantinos; Chrysohoou, Christina; Dilaveris, Polychronis; Gatzoulis, Konstantinos A; Tousoulis, Dimitrios
No abstract available